"W poszukiwaniu słów..." (Władysława Sebyły sądy o poezji) - Kobylska, Dorota (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2001)
The main purpose of this article is to show the general development of Władysław Sebyła’s works in his next tomes Pieśni szczurołapa (Song of the ratcatcher), Koncert egotyczny (Egotic concert), Obrazy myśli (Views of thoughts). Poetry for Sebyła is the way of finding a man, showing the truth about himself by means of a literal word. Like also expressing a beauty of a nature, world by leading a dialog with himself. Besides he is looking for new people with whom he could talk about the significance of life. He supports on the authority of Cyprian Kamil Norwid and Jan Lechoń. His poetry is not to give any answer to the problems but to ask neverending questions.